RSMVC: A NEW-SIMPLE METHOD TO SELECT THE CUTTING TOOL BASE ON MULTI CRITERIA - Xuan Thinh, Hoang; Van Dua, Tran (Journal of Applied Engineering Science, 2022)
The selection of the cutting tool material to be suitable for the workpiece material is usually based on the tables in the manuals or the manufacturer’s recommendations. Within each of these document types, the cutting tool materials were described by many criteria. The values of the criteria for each type of cutting tool can be a number, or a certain range. This study proposes a new method to rank and select cutting tools. First, a ranking of the solutions for each criterion will be performed. This ranking is based on the mean value of the criteria in each solution. Therefore, this method is called “Ranking the Solutions based on the Mean Value of Criteria - RSMVC”. The RSMVC method was proven to be a highly reliable method for ranking the cutting tool materials. These results were successfully verified when solving the problems in different cases of cutter material selection.